ANALISIS PERSEPSI KEAMANAN DATA DAN KEPUASAN PELANGGAN TERHADAP PENGGUNAAN DOMPET DIGITAL DANA DAN SHOPEEPAY DI KOTA TANGERANG - Sugiyanto, Eko; Cahyani, Firda Mutiara; Novitasari, Adifa Kurnia; Pramulanto, Himawan (JURNAL LENTERA BISNIS, 2026)
This study analyzes the influence of perceived data security and customer satisfaction on the use of digital wallets DANA and ShopeePay in Tangerang City. A quantitative survey approach was used with 110 respondents who actively use digital wallets. Data analysis used multiple linear regression with SPSS. The results show that perceived data security and customer satisfaction significantly influence the use of DANA both partially and simultaneously. In ShopeePay, customer satisfaction has a significant partial effect, while perceived data security does not show a partial effect but remains significant simultaneously. These findings highlight the importance of security systems and service quality in strengthening trust in digital payment systems